Dinâmica da produção de forragem e proteína bruta do capim bermuda sob adubação mineral e orgânica - Bratz, Vinicius Felipe (2020)
Chemical fertilizers are the most crucial inputs for enhancing yield of cultived pastures. The use of organic fertilizers can contribute to reduce there costs and make the productive systems more sustainable. This study evaluated the herbage yield, crude protein of forage, morphogenic variables and tiller density on Tifton 85 bermuda grass pasture based under different types of fertilizers. Five pastures were evaluated: (1) without fertilizer, control; (2) mineral fertilizer; (3) pig slurry (50%) + mineral fertilizer (50%); (4) cattle slurry (50%) + mineral fertilizer (50%) and (5) pig slurry (50%) + cattle slurry (50%). The experimental design was completely randomized with five treatments (type of fertilizer) and three replicates (plots) with repeated measures in time (data grouped by seasons/month). N-fertilized applied are limited on 200 kg N/ha/yr. The cuts were made 25 cm of canopy height. Samples were taken from de upper and lower stratum. Forage yields were 11.7; 21.4; 19.0; 19.6 and 16.6 t/ha/year; crude protein concentration were 12.4; 16.7; 15.3; 15.5 and 14.7%, respectively. Morphogenic variables and tiller density were more affected by seasons and months and indicate great potential of Tifton 85 bermuda grass in autumn. The highest best results were found by organo-mineral fertilization.